Youth and Old Age as Culturally Constructed Physical Identities: The Case of Czech Developmental Psychology of the Second Half of the Twentieth Century - Řídký, Josef (Dějiny – teorie – kritika, 2016)
In this study, youth and old age are viewed as culturally constructed physical identities, whereby the main focus is on the ways in which their representation was constructed within the discourse of Czech developmental psychology of the second half of the 20th century. The investigation is framed by the introduction of the term corpus, by which the author tries to highlight the specific nature of these physical identities. Corpus is defined by three groups of characteristics: it forms an inventory of characteristic qualities; it locates identity as something original in the human body; it treats the particular identities as separate animal species. On the axis of these groups, it turns out that developmental psychology disqualifies both youth and old age in favour of the dominant identity of adulthood. While youth has an adult body at its disposal, lack of experience and excessive emotivity make it questionable and it is perceived that they require control so as not to threaten a development into a future adult. Old age, on the other hand, is disqualified by weakness of the body and overabundance of experience, which turn it into a mere caricature of a former adult. Both identities are thus subjected to a symbolic adultocentrism.